Key messages from Safe Food, Fair Food: Food safety in informally marketed livestock products in sub-Saharan Africa - Makita, K.; Kang'ethe, Erastus K.; Zewde, G.; Kurwijila, Lusato R.; Matusse, H.; McCrindle, C.M.E.; Tano-Debrah, K.; Bonfoh, Bassirou; Costard, Solenne; Grace, Delia (2012)
In sub Saharan Africa (SSA), 85 to 90% of livestock products are distributed through informal marketing systems which are not always effectively regulated by state services. Food borne diseases (FBD) are potentially serious public health problems but rigorous implementation of food safety measures is difficult due to the limited resources and adverse effects on the livelihoods of actors along value chains. The Safe Food Fair Food project funded by Germany was conducted in 8 SSA countries between 2008 and 2011 to develop capacity in participatory risk assessment to improve food safety while enhancing market access by smallholder farmers. The main activities were food safety country situation analyses, participatory risk assessments and national stakeholder workshops. In total, 21 risk assessment studies were conducted for a variety of livestock products and hazards. Key messages from the project included (1) the realized importance of informal food chains in African economy; (2) risks were less serious than previously perceived; (3) participatory methods were found useful in risk assessment in resource poor SSA countries; and (4) necessity for trans-disciplinary research and action along value chain. In the next phase starting shortly, Safe food Fair food II, involvement of decision makers, integration of multiple-pathogens and socio-economics into risk assessment are hoped to make important changes in addressing food safety issues in sub Saharan Africa.